STRATEGY DIGITAL MARKETING, BRAND AMBASSADOR AND BUYING DICISION: THE CASE OF SCARLETT WHITENING - Ayu Farida; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
The purpose of this study was to determine Scarlett Whitening's marketing strategy in the Tik-tok and Instagram applications. The research method used is descriptive quantitative. This research is based on the theory of marketing strategy based on SWOT analysis. Scarlett Whitening used the Korean wave phenomenon, as an opportunity to promote its products and build a brand image. The mindset and way of life of the audience is of course indirectly influenced by South Korea's soft power which is exported to a number of countries in the form of K-Drama, K-Pop, K-Style, culinary, and technology. This research was conducted by observing and documenting Scarlett Whitening's Instagram and Tiktok uploads to find out the SWOT of the marketing strategies of the two applications. The results of this study indicate that marketing on the Instagram application has proven to be more effective when compared to Tiktok, as evidenced by the SWOT calculation results which show Instagram in quadrant III, which means it has many opportunities and few threats. In contrast, Tiktok is in quadrant II which means it has many threats.